Justifying dissent - Leonardo Bursztyn; Georgij V. Egorov; Ingar Haaland; Aakaash Rao; Christopher Roth (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
Dissent plays an important role in any society, but dissenters are often silenced through social sanctions. Beyond their persuasive effects, rationales providing arguments supporting dissenters' causes can increase the public expression of dissent by providing a "social cover" for voicing otherwisestigmatized positions. Motivated by a simple theoretical framework, we experimentally show that liberals are more willing to post a Tweet opposing the movement to defund the police, are seen as less prejudiced, and face lower social sanctions when their Tweet implies they had first read scientific evidence supporting their position. Analogous experiments with conservatives demonstrate that the same mechanisms facilitate anti-immigrant expression. Our findings highlight both the power of rationales and their limitations in enabling dissent and shed light on phenomena such as social movements, political correctness, propaganda, and anti-minority behavior.
Keywords: D83; D91; P16; J15; 330; Dissent; social image; rationales; social media